Penerapan Model Quantum Teaching Menggunakan Media Peta Konsep dalam Pembelajaran Struktur Atom di Kelas X SMA - Bajoka Nainggolan; Ruth Dharmayana Sinaga (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This study aims to determine learning outcome and collaborative character of students who are taught with Quantum Teaching Learning model  using concept maps media on Atomic Structure. Research population is science students of grade X , and samples selected were 30 students of experimental  and  control classes respectively. The test instrument 20 multiple choice questions, and a non-test observation sheet. Soft ware data is processed with SPSS 16.0 for Windows, acquired pre-test experimental class = control, post-test experimental> control (90 > 85). The mean gain experimental > control (0.805 > 0.693), improvement of learning outcomes experimental > control (80.5% > 69.6%). Hypothesis test (α = 0.05) t test ≥ t tab.. (5.563 > 0.687), mean improvement of learning outcomes chemistry student with QT > conventional. The mean of the experimental character of student collaboration 67.75 (good), control 57.00 (enough). Correlation of learning outcomes with student collaboration experiment 90.4% (very high), controls 60.5% (high), QT contribution to the learning outcomes and cooperation experimental class 81.7%, 36.6% control. Conclusions: The increase in the value of learning outcomes chemistry atomic structure and character of students taught by cooperative learning model QT higher than conventional methods. Keywords: quantum teaching learning, media concept map, atomic structure